Anti‐interleukin‐23 for psoriasis in elderly patients: guselkumab, risankizumab and tildrakizumab in real‐world practice. (1st March 2022) - Ruggiero, A.; Fabbrocini, G.; Cinelli, E.; Ocampo Garza, S. S.; Camela, E.; Megna, M.
Summary: Background: Elderly patients (aged ≥ 65 years) represent an increasing proportion of patients with psoriasis and 15% of these have moderate to severe disease. Biologics are being used frequently in this group of patients even though safety and efficacy data are limited. In addition, owing to anti‐interleukin (IL)‐23 therapies being a relatively recent option, no data have been reported about their use in elderly patients with psoriasis. Aim: To evaluate and compare the safety and efficacy of guselkumab, risankizumab and tildrakizumab in real‐world practice in elderly patients. Methods: This was a single‐centre retrospective study that enrolled patients aged ≥ 65 years with moderate to severe plaque psoriasis, treated with guselkumab, risankizumab or tildrakizumab. The length of the study for each group depended on the drug (44 weeks for risankisumab, 40 weeks for guselkumab and 28 weeks for tildrakizumab, owing to its more recent availability in Italy). Results: In total, 34 patients were enrolled ( n = 20 on guselkumab; n = 8 on risankizumab; n = 6 on tildrakizumab). At Week 4, 29.4% reached 90% improvement in Psoriasis Area and Severity Index (PASI90) and 8.8% reached 100% improvement in PASI (PASI100); at Week 28, PASI90 and PASI100 was reached by 58.8% and 29.4%, respectively. At the final follow‐up (Week 40 or 44, depending on drug), data were available only for the risankizumab (Week 40) and guselkumab (Week 44) and groups, and showed that 71.4% of patients had reached PASI90 and 53.5% had reached PASI100. Four patients (11.7%) discontinued treatment. No significant differences were found between the three groups. The limitations of the study included its retrospective nature of the study, small sample size, and different numbers of patients and follow‐up duration for the different groups (highest for guselkumab, lowest for tildrakizumab). Conclusion: The three anti‐IL‐23 therapies assessed are promising, safe and effective options in elderly patients, and there was no significant difference between them. However, more data are needed to confirm our results and to understand their role in the management of this group of patients.